Prediction of Relative Nutritive Value of Themeda Anathera (Nees Ex. Steud) Hack of Kumaun Hills from Its Chemical Composition at Different Stages of Growth - Pant, C.S.; Dhami, K.S. (Asian Journal of Chemistry, 2010)
Chemical investigation of indigenous fodder grass, viz., Themeda anathera (Nees ex. Steud) Hack was carried out at different stages of growth from July to October. This fodder grass was found to contain sufficiently high level of protein, ether extract (fat), sugars, ash and minerals and hence assessed as a good quality fodder.